Strength analysis and fatigue life estimation of composite pressure vessel (CPV) based on the residual strain energy (RSE) approach. Issue 2 (13th November 2020) - Kabiri Ataabadi, Abdulreza; Ahmadi Jeyed, Ghadir
Abstract: This study estimates the fatigue life of a composite pressure vessel (CPV) using the residual strain energy (RSE) method. At first, the CPV with different materials is analyzed applying finite element (FE) method to find the stress distribution and the critical region. Subsequently, through static analysis and RSE method coded in MATLAB environment, the fatigue life of the vessels is estimated. In addition, with the absence of experimental data, the sensitivity of fatigue life to curve fitting parameters is investigated. In the end, the obtained results indicate that the proposed method has an impressive performance and can be employed for fatigue analysis of the huge finite element models.